Anti-NMDA Receptor Encephalitis: Retrospective Analysis of 15 Cases, Literature Review, and Implications for Gynecologists. (15th March 2022) - Liu, Yibin; Tian, Yanpeng; Guo, Ruoyi; Xu, Xin; Zhang, Mingle; Li, Zhongkang; Xiao, Yanlai; Cao, Wen; Gao, He; Kong, Desheng; Du, Yanfang; Meng, Li; et al.
Abstract : Background . Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is a rare form of autoimmune encephalitis caused by anti-NMDA receptor antibodies. This disease mainly affects women of childbearing age and is commonly associated with ovarian teratoma. However, the relationship between anti-NMDA receptor encephalitis and ovarian teratoma and the role of anti-NMDA receptor antibody in the relationship remain unclear. Objectives . This study aimed to describe 15 cases of anti-NMDA receptor encephalitis (5 with ovarian teratoma), review literature, and reinforce the gynecologist's knowledge of this disorder. Methods . Clinical data of 15 patients from January 2015 to December 2020 admitted to The Second Hospital of Hebei Medical University were collected and analyzed. The diagnosis of anti-NMDA receptor encephalitis was based on the presence of anti-NMDA receptor antibodies in cerebrospinal fluid (CSF) and/or serum. Laparoscopic teratoma removal was performed in patients with ovarian teratoma. All patients had received immunotherapy. In addition, a review of the literature was performed to reinforce the gynecologist's knowledge of this disorder. Results . A total of 15 patients with anti-NMDA receptor encephalitis were screened, of whom 5 patients were confirmed with ovarian teratoma by pathology. The most common symptoms of anti-NMDAR encephalitis with teratoma are fever (5/5, 100%), seizure (5/5, 100%), mental and behavioral disorders (4/5, 80%), and decreased consciousness (4/5, 80%). Conversely, the most common symptoms of patients without teratoma were neuropsychiatric symptoms, including headache (6/10, 60%) and mental and behavioral disorders (7/10, 70%). All patients underwent immunotherapy, including steroids, intravenous immunoglobulin (IVIG), plasma exchange, and cyclophosphamide, and 4 out of 5 patients with ovarian teratomas underwent surgical treatment. All patients had a good outcome after systemic, surgical, and immunotherapy treatment. No patient who underwent surgical treatment developed a recurrence. Conversely, 2 of 10 patients without teratoma developed an anti-NMDA receptor encephalitis recurrence. Conclusions . Patients with anti-NMDA encephalitis show severe mental and neurological symptoms. Resection of teratoma is beneficial to the relief or disappearance of symptoms and has a good prognosis. This disorder should be fully recognized by gynecologists, who play an important role in diagnosis and treatment.